Answer:
6 C(s) + 3 O₂(g) + 2 Fe₂O₃(s) → 4 Fe(s) + 6 CO₂(g)
Explanation:
In the first step, carbon and oxygen react to form carbon monoxide:
2 C(s) + O₂(g) → 2 CO(g)
In the second step, iron(III) oxide and carbon monoxide react to form iron and carbon dioxide:
Fe₂O₃(s) + 3 CO(g) → 2 Fe(s) + 3 CO₂(g)
In the net chemical equation doesn't appear CO, which is an intermediary. To achieve it, we will multiply the first step by 3, the second step by 2, and add them.
6 C(s) + 3 O₂(g) → 6 CO(g)
+
2 Fe₂O₃(s) + 6 CO(g) → 4 Fe(s) + 6 CO₂(g)
----------------------------------------------------------------
6 C(s) + 3 O₂(g) + 2 Fe₂O₃(s) + 6 CO(g) → 6 CO(g) + 4 Fe(s) + 6 CO₂(g)
6 C(s) + 3 O₂(g) + 2 Fe₂O₃(s) → 4 Fe(s) + 6 CO₂(g)